VERBAL AND NONVERBAL WORDS IN GENDER LINGUISTICS - Nunnanova Gulshaydo Bekpulatovna (PEDAGOGS, 2024)
Abstract: This study discusses the issue of the importance of the verbal and nonverbal communication in gender linguistics.